Retrospektywna perspektywa badań prowadzonych przez Alice Miller nad związkami czarnej pedagogiki i znaczeniem relacji rodzinnych dla kształtowania się postaw społecznych wspierających nazizm i faszyzm - Tabernacka, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
A retrospective analysis of the conditions that influenced the emergence of Nazism and fascism indicates that one of the factors that fostered the emergence of both systems were specific family relationships and the upbringing currently referred to as black pedagogy. Alice Miller claimed that the full subordination of children to the will of adults, resulting from the use of mechanisms of black pedagogy, led to the subsequent political subordination, which was an element of social relations in the totalitarian system of the Third Reich. Miller noticed the roots of black pedagogy in the educational tendencies present in the German cultural circle as early as the 18th century, and she noticed ethnocentric conditions based on black pedagogy, also in the post-war period. The contemporary international legal standard for the protection of the subjectivity of the child should contribute to the creation of systemic and cultural barriers against black pedagogy and its consequences.
Keywords: wychowanie; czarna pedagogika; Alice Miller; faszyzm; nazizm